Asprosin in umbilical cord of newborns and maternal blood of gestational diabetes, preeclampsia, severe preeclampsia, intrauterine growth retardation and macrosemic fetus - Baykus, Yakup; Yavuzkir, Seyda; Ustebay, Sefer; Ugur, Kader; Deniz, Rulin; Aydin, Suleyman (Elsevier Science Inc, 2019)
Pathological pregnancies, such as gestational diabetes, preeclampsia, severe preeclampsia, intrauterine growth retardation and macrosomic fetuses, are among the most fundamental problems of obstetrics clinics that are risk factors for both mother and child. Our main goal here is to compare maternal blood and newborn venous-arterial cord blood asprosin levels in pathological and healthy pregnancies. The study included 30 pregnant women with gestational diabetes, 30 with preeclampsia, 30 with severe preeclampsia, 30 with intrauterine growth retardation, 29 with macrosomic fetuses and 30 healthy pregnant women. All mothers were voluntary participants. Arteries and venous blood samples from both mothers and newborns were taken, in which asprosin levels were measured by ELISA. There was a statistically significant increase in asprosin levels in pregnant women with gestational diabetes, preeclampsia, severe preeclampsia and macrosemic fetuses compared with the control group, whereas in those with intrauterine growth retardation a significant decrease was observed. Venous and arterial cord blood asprosin levels were also close to maternal asprosin levels. Regarding the asprosin levels in venous and arterial cord blood in all newborns, the former was higher, but was not statistically significant.
Keywords: Asprosin; Umbilical cord; Gestational diabetes; Pregnancy; Preeclampsia; Intrauterine growth retardation; Macrosomic fetuses